Comparison of Post-Operative Analgesic Effects of Intrathecal Dexmeditomidine Versus Intrathecal Ketamine Added to Bupivacaine in Total Knee Replacement Surgeries - Hasnain, Fahad; Saeed, Munim; Shah, Syed Qasim Ali; Riaz, Muhammad Mohsin; Khalil, Waqas; Sharif, Muhammad Huzaifa (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the analgesic efficacy of Dexmedetomidine versus Ketamine when added to intrathecal Bupivacaine in patients undergoing unilateral total knee replacement surgery.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Anesthesia, Combined Military Hospital, Rawalpindi, Pakistan, from May to Oct 2022.Methodology: Our study enrolled a total of 80 patients, divided into Dexmedetomidine group (n=40) and Ketamine group (n=40) group using non-probability consecutive sampling. Patients in both groups received 2.5 ml of 0.5% Bupivacaine with Dexmedetomidine group receiving 5 mcg (0.5 ml) of the drug and Ketamine group 0.1 mg/kg of Ketamine in 0.5 ml to a total volume of 3 ml. Data analysis was performed using SPSS 26.0, with significance set at p≤0.05.Results: Time of onset for sensory block in Dexmedetomidine group was delayed than Ketamine group with mean time of onset 4.34±0.14 minutes versus 3.38±0.10 minutes (p